GENDER INEQUALITY REPRESENTED IN ENGLISH TEXTBOOKS: A LITERATURE REVIEW - Mihira, Luh Shanti Nilayam; Suwastini, Ni Komang Arie; Artini, Ni Nyoman; Jayantini, I Gusti Agung Sri Rwa; Budiarta, I Wayan (Universitas Pendidikan Ganesha, 2021)
Ideologies are contested through discourses; thus, textbooks can be a fertile ground for implanting the prevalence of women's marginalization in society, or they can also be used for deconstructing the ideology. The present study aims to provide a general map of how English as a foreign language reflects gendered stereotypes. The study was library research that used the results of previous studies to answer the research questions. Using George's method, the study chose thirty articles published in 2010 - 2021, then critically reviewed. The critical reading was continued with mapping the results of the studies, and their arguments on gender stereotypes included English as Foreign Language textbooks worldwide. The review revealed that there had been prevalent marginalization of women in English textbooks reflected through the depiction of women as less dominant, inferior than men, primarily domestic, generally weak, powerless, voiceless, and passive. Such male prevalence was also found in Indonesian EFL textbooks. Many previous studies admit that male prevalence and women marginalization in EFL textbooks reflect reality in society. Nevertheless, the present study takes the standpoint that calls for the utilization of textbooks to deconstruct gendered binary oppositions that marginalize women by deliberately designing textbooks that impart awareness about gender equity.